4x-6(2x-1)=2

Simple and best practice solution for 4x-6(2x-1)=2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x-6(2x-1)=2 equation:


Simplifying
4x + -6(2x + -1) = 2

Reorder the terms:
4x + -6(-1 + 2x) = 2
4x + (-1 * -6 + 2x * -6) = 2
4x + (6 + -12x) = 2

Reorder the terms:
6 + 4x + -12x = 2

Combine like terms: 4x + -12x = -8x
6 + -8x = 2

Solving
6 + -8x = 2

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + -6 + -8x = 2 + -6

Combine like terms: 6 + -6 = 0
0 + -8x = 2 + -6
-8x = 2 + -6

Combine like terms: 2 + -6 = -4
-8x = -4

Divide each side by '-8'.
x = 0.5

Simplifying
x = 0.5

See similar equations:

| -16-6.5= | | 6n^2-18-18=6 | | r+0.12=0.20 | | -4.9=-5.7+x | | m+4=-6.7 | | 4.11x=16 | | 3c+12-c=78 | | 12-(-17)= | | 3(-2x+1)=21 | | -9-3x=-5x+7 | | x-9=6x+6 | | 0.9+0.3x=2.4 | | 4x+2=142 | | 2x-(3-x)=5+6x | | 2x^2=15-x | | 4x-(x+3)=15 | | 7=(-5-m)+4(6-m) | | -8+(-15)=(-15)+(-8) | | 15x=12(x-3) | | 5x+5+6x=5 | | -3m+4+5m=-6 | | 10x-9=-2x-69 | | 20x^3=50x | | 6(x-9)+x=7(x-9)+9 | | 3x+5=5(x-3) | | (2x+11y)(4x-9y)= | | 0=x^3-19x+18 | | 2x^2+15x=-7 | | 5(c+.80)+6=50 | | 2a+30=4a-4 | | 20+57x-9x^2=0 | | 7(2x-3)=7 |

Equations solver categories